The Poems of Archibald Lampman - Lampman, Archibald (Heritage., 1974)
This volume includes The Poems of Archibald Lampman, a collection of 237 opems edited with a memoir by Duncan Campbell Scott after Lampman's death, and At the Long Sault and Other New Poems, which was hailed, when it first appeared in 1943, as 'the literary discovery of the year.'